Senescent Mesenchymal Stem Cells in Myelodysplastic Syndrome: Functional Alterations, Molecular Mechanisms, and Therapeutic Strategies - Chen, Xiaofang; Li, Ningyu; Weng, Jianyu; Du, Xin (Frontiers in Cell and Developmental Biology, 2021)
Myelodysplastic syndrome (MDS) is a group of clonal hematopoietic disorders related to hematopoietic stem and progenitor cell dysfunction. But the therapies which targeted hematopoietic stem cells still can’t work effectively; what they can solve is slowing the evolution to acute myeloid leukemia instead of eradicate the disease. Mesenchymal stromal cells (MSCs) have been identified as one of the main cellular components of the bone marrow microenvironment holding an indispensable role for normal hematopoiesis. During aging, MSCs diminish their functional and regenerative capacities and in some cases encounter replicative senescence, promoting inflammation and cancer progression. Recent studies related the contribute of bone marrow microenvironment and Mesenchymal Stem Cells to the progress of the disease offer us an new insight into myelodysplastic syndrome This review is going to present the latest updates about the role of the mesenchymal stem cells in myelodysplastic syndrome treatment.